Los derechos antidumping y el doble castigo para el importador - Kihara Nomura, Adriana (2019)
The Tax Court has repeatedly confirmed that antidumping duties are not part of the cost of acquiring imported artifacts. However, Supreme Decree 006-2003-PCM indicates that these rights have the status of a fine towards the importer. The disparity of the topic is clear. In this article, the author questions the Supreme Decree and focuses on assessing if the antidumping duties are a punishable conduct. In order to do this, the author explains the concept of dumping and takes as reference both legislation and legal doctrine on the subject. It is argued that, if there is no punishable conduct, antidumping duties cannot be classified as fines or penalties. In addition, it is proposed that these, being compensatory duties paid on importation, must belong to the cost of acquiring the product in order not to establish a double tax penalty.